Safety and efficacy of antenatal milk expressing for women with diabetes in pregnancy: protocol for a randomised controlled trial. Issue 10 (30th October 2014) - Forster, Della A; Jacobs, Susan; Amir, Lisa H; Davis, Peter; Walker, Susan P; McEgan, Kerri; Opie, Gillian; Donath, Susan M; Moorhead, Anita M; Ford, Rachael; McNamara, Catharine; Aylward, Amanda; et al.
Abstract : Introduction: Many maternity providers recommend that women with diabetes in pregnancy express and store breast milk in late pregnancy so breast milk is available after birth, given (1) infants of these women are at increased risk of hypoglycaemia in the first 24 h of life; and (2) the delay in lactogenesis II compared with women without diabetes that increases their infant's risk of receiving infant formula. The Diabetes and Antenatal Milk Expressing (DAME) trial will establish whether advising women with diabetes in pregnancy (pre-existing or gestational) to express breast milk from 36 weeks gestation increases the proportion of infants who require admission to special or neonatal intensive care units (SCN/NICU) compared with infants of women receiving standard care. Secondary outcomes include birth gestation, breastfeeding outcomes and economic impact. Methods and analysis: Women will be recruited from 34 weeks gestation to a multicentre, two arm, unblinded randomised controlled trial. The intervention starts at 36 weeks. Randomisation will be stratified by site, parity and diabetes type. Women allocated to the intervention will be taught expressing and encouraged to hand express twice daily for 10 min and keep an expressing diary. The sample size of 658 (329 per group) will detect a 10% difference in proportion of babies admitted to SCN/NICU (85% power, α 0.05). Data are collected at recruitment (structured questionnaire), after birth (abstracted from medical record blinded to group), and 2 and 12 weeks postpartum (telephone interview). Data analysis: the intervention group will be compared with the standard care group by intention to treat analysis, and the primary outcome compared using χ 2 and ORs. Ethics and dissemination: Research ethics approval will be obtained from participating sites. Results will be published in peer-reviewed journals and presented to clinicians, policymakers and study participants. Trial registration number: Australian Controlled Trials Register ACTRN12611000217909.